The Profile Of Secondary School Students’ Written Mathematical Communication Through Problem Solving Assessment Viewed From Differences In Mathematical Ability - Usman, Muhammad Rizal; Husniati, Andi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The aim of this study is to examine problem-solving assessments to measure the profile of students' written mathematical communication skills across low, medium, and high ability levels. The problem-solving assessment used includes a problem-solving test and an interview guide. This study is descriptive research with a qualitative approach. The research subjects consist of three students: one with low mathematical ability, one with medium mathematical ability, and one with high mathematical ability. High-ability students meet four indicators of written mathematical communication skills, which include writing down the known information and questions from the given problem and sketching a diagram, understanding mathematical ideas in planning and formulating rules or presenting formulas, interpreting information in carrying out the problem-solving plan, and reviewing/checking the correctness of the answers/conclusions. Medium-ability students meet one indicator of written mathematical communication skills, which is understanding mathematical ideas to plan and formulate rules or present formulas. Low-ability students do not meet any of the indicators of written mathematical communication skills